Transcriptomic changes during stage progression of mycosis fungoides: from translational analyses to their potential clinical implications. (1st March 2022) - Dobos, G.; Assaf, C.
Abstract: Linked Article: Xiao et al. Br J Dermatol 2022; 186 :520–531 .